2018
DOI: 10.1016/j.redox.2017.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Carnosine attenuates cyclophosphamide-induced bone marrow suppression by reducing oxidative DNA damage

Abstract: Oxidative DNA damage in bone marrow cells is the main side effect of chemotherapy drugs including cyclophosphamide (CTX). However, not all antioxidants are effective in inhibiting oxidative DNA damage. In this study, we report the beneficial effect of carnosine (β-alanyl-l-histidine), a special antioxidant with acrolein-sequestering ability, on CTX-induced bone marrow cell suppression. Our results show that carnosine treatment (100 and 200 mg/kg, i.p.) significantly inhibited the generation of reactive oxygen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 34 publications
(35 reference statements)
0
40
0
Order By: Relevance
“…The oxidative DNA damage in cells is the main side effect of chemotherapy drugs including cyclophosphamide [ 6 ]. The modulation of oxidative stress and inflammatory cytokine production through stimulation of immunity may help in maintaining a disease-free state [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidative DNA damage in cells is the main side effect of chemotherapy drugs including cyclophosphamide [ 6 ]. The modulation of oxidative stress and inflammatory cytokine production through stimulation of immunity may help in maintaining a disease-free state [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally, chemotherapeutics drugs often generate many harmful side effects such as cytotoxic effects and host immunosuppression, no matter how great of their therapeutic effects are [ 4 ]. Cyclophosphamide (Cy), an alkylating agent, has been widely used as chemotherapeutic drug which results in a lot of adverse effects including immunosuppression, bone marrow suppression, leucopenia and oxidative stress [ 5 , 6 , 7 , 8 ]. It has been reported that Cy can generate oxidative stresses, mediate disruption of the redox balance, and lead to biochemical and physiological disturbances [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclophosphamide (CY), an alkylating agent, has been most widely used to treat autoimmune diseases and cancer [ 14 , 15 ]. CY is also a cytotoxic drug, but it has no activity in vitro, and it can damage the structure of DNA, cut off its copy that can lead to cell death in vivo [ 16 , 17 ]. Research showed that the long-term use of CY had harmful side effects, such as immunosuppression, myelosuppression and leucopenia [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The liver is the main drug metabolism organ in mammals. Metabolized cyclophosphamide causes damage to mitochondria and damage to cellular respiration, which affects the onset of lipid peroxidation and an increase in reactive oxygen species [33,34]. In this work, signi cant increases in Liver index were observed through the impact of cyclophosphamide, and this altered were regulated by Lvjiao Buxue Granules' treatment.…”
Section: Organ Indexesmentioning
confidence: 66%